2022
DOI: 10.3390/cancers14246106
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of High-Risk Extramedullary Relapse Factors in Newly Diagnosed MM Patients

Abstract: Extramedullary relapse of multiple myeloma (MM) is often resistant to existing treatments, and has an extremely poor prognosis, but our understanding of extramedullary relapse is still limited. The incidence, clinical characteristics, impact on the prognosis of extramedullary relapse, and the risk factors for extramedullary relapse in NDMM patients were analyzed. Among the 471 NDMM patients, a total of 267 patients had disease relapse during follow-up, including 64 (24.0%) patients with extramedullary relapse.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…The aggressive stage of MM is characterized by extramedullary MM (EMM), which was reported in roughly 7% of NDMM and increased to 30% of patients with relapse [165]. After a series of molecular alterations, the clonal cells of the MM disease were able to escape from the bone marrow and migrate via the circulatory system to access and grow independently in other organs and tissues [166].…”
Section: Extramedullary MMmentioning
confidence: 99%
“…The aggressive stage of MM is characterized by extramedullary MM (EMM), which was reported in roughly 7% of NDMM and increased to 30% of patients with relapse [165]. After a series of molecular alterations, the clonal cells of the MM disease were able to escape from the bone marrow and migrate via the circulatory system to access and grow independently in other organs and tissues [166].…”
Section: Extramedullary MMmentioning
confidence: 99%
“…showed that among newly diagnosed MM patients where ASCT was used, 57% had disease relapse during follow-up, including 24% of patients with EM relapse. [ 33 ] EM relapse of MM is often resistant to existing treatments and has an extremely poor prognosis. [ 8 , 33 ] Survival analysis showed that EM relapse patients had significantly worse median overall survival than patients with relapse but without EM involvement.…”
Section: Discussionmentioning
confidence: 99%
“…[ 33 ] EM relapse of MM is often resistant to existing treatments and has an extremely poor prognosis. [ 8 , 33 ] Survival analysis showed that EM relapse patients had significantly worse median overall survival than patients with relapse but without EM involvement. [ 33 ] Plasmacytoma occurrence at relapse in patients with upfront ASCT is significantly associated with a poor prognosis.…”
Section: Discussionmentioning
confidence: 99%